Odpowiedzi

2010-03-16T22:52:35+01:00
A)
4(x-3) = 20
4x-12 = 20
4x = 20+12
4x = 32 |:4
x = 8

b)
-3(x-2) = -12
-3x+6 = -12
-3x = -18 |:(-3)
x = 6

c)
6(2x+1) = 3(3x-8)
12x+6 = 9x-24
12x-9x = -24-6
3x = -30 |:3
x = -10

d)
-3(3x-1)-3 = -4
-9x+3-3 = -4
-9x = -4 |:(-9)
x = 4/9

e)
4(x-2)-3(x-1) = 2(x+6)
4x-8-3x+3 = 2x+12
x-5 = 2x+12
x-2x = 12+5
-x = 17 |:(-1)
x = -17

f)
3k-(10+k) = 8
3k-10-k = 8
2k = 8+10
2k = 18 |:2
k = 9
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-16T22:53:32+01:00
A) 4(x-3)=20
4x-12=20
4x=20+12
4x=32 /:4
x=8

b)-3(x-2)=-12
-3x+6=-12
-3x=-12-6
-3x=-18 /:(-3)
x=6

c)6(2x+1)=3(3x-8)
12x+6=9x-24
12x-9x=-24-6
3x=-30 /:3
x=-10

d)-3(3x-1)-3=-4
-9x+3-3=-4
-9x=-4 /:(-9)
x=4/9

e)4(x-2)-3(x-1)=2(x+6)
4x-8-3x+3=2x+12
4x-3x-2x=12+8-3
-x=17 /:(-1)
x=-17

f)3k-(10+k)=8
3k-10-k=8
3k-k=8+10
2k=18 /:2
k=9
2 5 2
2010-03-16T22:56:34+01:00
A)4(x-3)=20
4x-12=20
4x=20+12
4x=32/:4
x=8

b) -3(x-2)= -12
-3x+6=-12
-3x=-12-6
-3x=-18/:-3x
x=6

c)6(2x+1)=3(3x-8)
12x+6=9x-24
12x-9x=-24-6
3x=-30/:3
x=-10

d) -3(3x-1)-3= -4
-9x+3-3=-4
-9x=-3+3-4
-9x=-4/:-9
x=4/9

e) 4(x-2)-3(x-1)=2(x+6)
4x-8-3x+3=2
4x-3x=8-3+2
x=7/:1 x=7

f) 3k-(10+k)=8
3k-10-k=8
2k=10+8
2k=18/:2
k=9